Smoking as an 'informed choice': implications for endgame strategies. Issue 6 (24th October 2016) - Hoek, Janet; Ball, Jude; Gray, Rebecca; Tautolo, El-Shadan
Abstract : Objective: Tobacco companies often assert that adults should be free to make an 'informed choice' about smoking; this argument influences public perceptions and shapes public health policy agendas by promoting educative interventions ahead of regulation. Critically analysing 'informed choice' claims is pivotal in countries that have set endgame goals and require new, more effective policies to achieve their smoke-free aims. Methods: In-depth interviews with 15 New Zealand politicians, policy analysts and tobacco control advocates examined how they interpreted 'informed choice' arguments. We used a thematic analysis approach to review and explicate interview transcripts. Results: Participants thought 'informed choice' implied that people make an active decision to smoke, knowing and accepting the risks they face; they rejected this assumption and saw it as a cynical self-justification by tobacco companies. Some believed this rhetoric had countered calls for stronger policies and thought governments used 'informed choice' arguments to support inaction. Several called on the government to stop allowing a lethal product to be widely sold while simultaneously advising people not to use it. Conclusions: 'Informed choice' arguments allow the ubiquitous availability of tobacco to go unquestioned and create a tension between endgame goals and the strategies used to achieve these. Reducing tobacco availability would address this anomaly by aligning government's actions with its advice.